2003
DOI: 10.1001/archpsyc.60.10.983
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Mediodorsal, Pulvinar, and Centromedian Nuclei of the Thalamus in Patients With Schizophrenia

Abstract: Background: Postmortem and magnetic resonance imaging (MRI) data have suggested volume reductions in the mediodorsal (MDN) and pulvinar nuclei (PUL) of the thalamus. The centromedian nucleus (CMN), important in attention and arousal, has not been previously studied with MRI.Methods: A sample of 41 patients with schizophrenia (32 men and 9 women) and 60 healthy volunteers (45 men and 15 women) underwent assessment with highresolution 1.2-mm thick anatomical MRI. Images were differentiated to enhance the edges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 42 publications
6
40
1
1
Order By: Relevance
“…Indeed, this hypothesis is supported by several studies showing reduced thalamic volume in patients with schizophrenia (Alelú-Paz & Giménez-Amaya, 2008; Andreasen et al, 1994;Byne et al, 2001Byne et al, , 2009Csernansky et al, 2004;Kemether et al, 2003;Konick & Friedman, 2001;Mitelman et al, 2006;Staal et al, 1998). However, not all studies have documented gross thalamic abnormalities (Lesch & Bogerts, 1984); rather, the majority point to specific changes in signaling between mediodorsal, anterior, and pulvinar thalamic nuclei (Byne et al, 2001(Byne et al, , 2002Danos et al, 2005;Kemether et al, 2003;Mitelman et al, 2006;Qiu, Zhong, Graham, Chia, & Sim, 2009). …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Indeed, this hypothesis is supported by several studies showing reduced thalamic volume in patients with schizophrenia (Alelú-Paz & Giménez-Amaya, 2008; Andreasen et al, 1994;Byne et al, 2001Byne et al, , 2009Csernansky et al, 2004;Kemether et al, 2003;Konick & Friedman, 2001;Mitelman et al, 2006;Staal et al, 1998). However, not all studies have documented gross thalamic abnormalities (Lesch & Bogerts, 1984); rather, the majority point to specific changes in signaling between mediodorsal, anterior, and pulvinar thalamic nuclei (Byne et al, 2001(Byne et al, , 2002Danos et al, 2005;Kemether et al, 2003;Mitelman et al, 2006;Qiu, Zhong, Graham, Chia, & Sim, 2009). …”
Section: Discussionmentioning
confidence: 89%
“…In fact, the largest postmortem study (Cullen et al, 2003) found no difference in the MDN volume, the number of MDN neurons, or the size of individual neurons. Alternatively, a large scale MRI study by Kemether et al (2003) did find significantly smaller MDNs in patients with schizophrenia. These conflicting results have been assessed by Danos et al (2005), who also found a moderate volume reduction in the left MDN, but not in neuron density or the total number of neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a deficit of visual cortex activation might derive from a thalamic dysfunction, which has been replicated in schizophrenia (Pakkenberg 1992;Andreasen et al 1994;Buchsbaum et al 1996;Young et al 2000). Indeed, a decreased volume of the pulvinar nucleus of the thalamus, a key component of the visual system, has been recently reported in schizophrenia using both MRI (Kemether et al 2003) and post-mortem (Byne et al 2002) assessments. Thus, the increased activation of the occipital cortex with clozapine may reflect an improvement in thalamic function, in line with a report of clozapine-induced Fos in the midline thalamic nuclei (Cohen and Wan 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Of interest, pulvinocortical disconnections were found in SZ patients and authors postulate that this feature could be related to the visual attention deficit often observed in SZ (Luck & Gold, 2008;Mitelman et al, 2006). Moreover, many studies demonstrated that the total neuron number and the volume of the pulvinar were diminished in schizophrenia (Byne et al, 2002(Byne et al, , 2007Kemether et al, 2003) and that glucose metabolism was reduced in this structure among unmedicated schizophrenia patients (Buchsbaum et al, 2007;Hazlett et al, 2004) supporting potential impairments of the pulvinar in schizophrenia.…”
Section: The Relay Structuresmentioning
confidence: 98%